FINITE ELEMENT ANALYSIS ON THE NONLINEAR BEHAVIOR OF THE RC SHEAR WALL WITH REGULAR OPENINGS INFLUENCED BY HIGH-STRENGTH STEEL - Ika Salsabila Nurahida; Bambang Piscesa; Pujo Aji; Asdam Tambusay (Journal of Civil Engineering, 2022)
This paper presented a nonlinear finite element analysis of lateral loading RC shear walls with regular openings using the 3D-NLFEA program. The RC shear walls model was generated from the available test results in the literature. To model the concrete under a complex stress state, a multi-surface plasticity model which combines compression failure surface with tension cut-off failure surface was used. The model was intended to look at the load-displacement relationship and the crack pattern between the model and the numerical model. In addition to the numerical model verification, parametric studies were carried out to investigate the use of high-strength steel (HSS) of the two different grades (grades 100 and 120) to replace all the normal-strength steel (NSS) or only some of it. The parametric studies found that the shear wall with the NSS bar demonstrated higher stiffness and achieved higher lateral load with the lowest extent of damage (compared to the RC shear wall with the HSS bar). On the other hand, using the HSS bar resulted in lower stiffness, lower lateral load, and higher damage region, which was expected as more strain is required to yield the HSS bar.